MISIOLOGI SEBAGAI ALAT TRANSFORMASI SOSIAL DALAM PENDIDIKAN AGAMA KRISTEN - Anton Ramba; Asra Leoni Tambing; Kristina; Yosi Rosita Karmila; Febidriati Rara' (CV. ADIBA AISHA AMIRA, 2024)
This study, titled